Current methods of bruxism diagnosis: A short communication - Pigozzi, Lucas B.; Rehm, Daniela D.S.; Fagondes, Simone C.; Pellizzer, Eduardo P. [UNESP]; Grossi, Márcio L. (Quintessence Publishing, 2019)
Purpose: To assess the current diagnostic methods for sleep bruxism (SB). Materials and Methods: This review of the literature evaluates all available instrumental and noninstrumental methods of bruxism/SB diagnosis. Results: SB diagnosis can be performed using self-reports and clinical examination, but these methods have little agreement with polysomnography. Two portable electromyography/electrocardiography appliances have been validated against polysomnography (BiteStrip and Bruxoff), but they are indicated only for primary SB. Polysomnography is considered the gold standard and is indicated for secondary SB; however, it is expensive and time-consuming. Conclusion: No perfect method of SB diagnosis exists, and future research should concentrate on improving SB self-reports.